2017
DOI: 10.1007/s10803-017-3108-2
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Letters in ASD: High Stimulus Variability Under Different Attentional Modes

Abstract: Studies using hierarchical patterns to test global precedence and local-global interference in individuals with ASD have produced mixed results. The current study focused on stimulus variability and locational uncertainty, while using different attentional modes. Two groups of 44 children with and without ASD completed a divided attention task as well as a global and local selective attention task. The results revealed global-to-local and local-to-global interference in ASD, to the same extent as in the TD gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The papers in this special section by Booth and Happé (2017), together with a recent publication elsewhere in this journal by Guy et al (2017) are sympathetic to what is now called "weak coherence" (Happé and Frith 2006) and the EPF accounts respectively and give up-to-date interpretations of them in the light of more recent findings, particularly as viewed through the lens of the Van der Hallen et al (2015) meta-analysis. Interestingly, both studies confirm the finding of Van der Hallen et al (2015) that the most robust difference between ASD and TD populations in this context is local-to-global interference in the temporal component of visual processing, although, in typical fashion for the field, a more-recent study by Van der Hallen et al (2017b) has not confirmed this result in a larger group. Van Eylen et al (2017) provide a theoretically agnostic comparison of local versus global processing abilities in ASD and TD individuals using a battery of tests on a large, well-characterized group.…”
supporting
confidence: 53%
“…The papers in this special section by Booth and Happé (2017), together with a recent publication elsewhere in this journal by Guy et al (2017) are sympathetic to what is now called "weak coherence" (Happé and Frith 2006) and the EPF accounts respectively and give up-to-date interpretations of them in the light of more recent findings, particularly as viewed through the lens of the Van der Hallen et al (2015) meta-analysis. Interestingly, both studies confirm the finding of Van der Hallen et al (2015) that the most robust difference between ASD and TD populations in this context is local-to-global interference in the temporal component of visual processing, although, in typical fashion for the field, a more-recent study by Van der Hallen et al (2017b) has not confirmed this result in a larger group. Van Eylen et al (2017) provide a theoretically agnostic comparison of local versus global processing abilities in ASD and TD individuals using a battery of tests on a large, well-characterized group.…”
supporting
confidence: 53%
“…It is noteworthy that the ASD population exhibits considerable heterogeneity. Indeed, impaired global processing is not common across the entire ASD population[Simmons et al, 2009;Van der Hallen, Vanmarcke, Noens, & Wagemans, 2017]. Further studies are needed to investigate links between sensory processing patterns, local/global precedence in visual processing, and face processing in ASD.…”
mentioning
confidence: 99%
“…Regarding the debate on whether ASD is associated with a global processing deficit, some studies suggested that global processing is not impaired but less preferred in ASD, because whether the processing is impaired or enhanced depends on a default preference to processing local information, or instruction of allocation of attention (Happé & Booth, 2008; Plaisted et al, 1999). Evidence shows that individuals with ASD exhibited better performance on the local than the global information when they were instructed to attend to both the local and global levels (Plaisted et al, 1999), or given a free‐choice (Koldewyn et al, 2013); however, when they were instructed to attend to either local or global information, they showed comparable performance on attentive information, no matter what level it was (Plaisted et al, 1999; Van der Hallen et al, 2017). Therefore, the global deficit has been interpreted as a disinclination, rather than a disability in ASD (Koldewyn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%